Political Institutions and Policy Choices: Evidence from the United States - Besley, Timothy; Case, Anne (Journal of Economic Literature, 2003)
A rich array of institutional diversity makes the United States an excellent place to study the relationship between political institutions and public policy outcomes.This essay has three main aims.First, it reviews existing empirical evidence on the relationship between institutional rules, political representation and policy outcomes.It aims to place the literature into a broader context of theoretical and empirical work in the field of political economy.Second, it develops a parallel empirical analysis that updates studies in the literature and re-examines some of the claims made, in a setting unified both in terms of policy outcomes and the period under study.Third, the paper develops some new directions for research, presenting a small number of novel exploratory results.